1998
DOI: 10.1097/00001756-199808030-00043
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin D28k expression in immunohistochemically identified Renshaw cells

Abstract: Double immunofluorescence was utilized to determine whether Renshaw cells contain calbindin D28k immunoreactivity. Renshaw cells were identified by their characteristic expression patterns of gephyrin immunoreactivity in sections of rat and cat lumbar spinal cord. In the rat, all neurons classified as Renshaw cells (n = 487) also contained calbindin D28k-immunoreactivity, and all calbindin D28k-immunoreactive cells located in the ventral-most region of lamina VII expressed the characteristic gephyrin labeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 13 publications
9
73
0
3
Order By: Relevance
“…(i) They were characterized as being large neurons located in the ventral horn that could be activated antidromically from the ventral root. In accordance with classical criteria, the antidromic spike followed high stimulus frequencies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) with no jitters in the activation latencies (see Fig. 1b).…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…(i) They were characterized as being large neurons located in the ventral horn that could be activated antidromically from the ventral root. In accordance with classical criteria, the antidromic spike followed high stimulus frequencies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) with no jitters in the activation latencies (see Fig. 1b).…”
Section: Methodssupporting
confidence: 80%
“…Recorded cells were filled intracellularly with Alexa Fluor dyes ( Fig. 1c; Alexa Fluor 488 or 588), which also allowed us to confirm their identity as RCs because of their expression of calbindin (13) (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…1 A). RCs also show specific calbindin 28k immunoreactivity (Carr et al, 1998), as shown in Figure 1, Ac and Ad. GFP-positive cells in the ventral cord were visually patched in the L2 (Fig.…”
Section: Identification Of Rcsmentioning
confidence: 71%
“…These nuclei are associated with the following muscles: soleus (SOL), medial gastrocnemius (MG), lateral gastrocnemius (LG) and tibialis anterior (TA). The total number of neurons simulated for these nuclei is shown in Table 1, based on estimates from human and cat literature (Feinstein et al 1955;Cooper 1966;Ariano et al 1973;Johnson et al 1973;Buchthal and Schmalbruch 1980;Dum and Kennedy 1980;McComas 1991;Jankowska 1992;Carr et al 1998;Banks 2006). Interneuron numbers are underestimated, in order to improve system performance.…”
Section: Methodsmentioning
confidence: 99%